Development of an Interactive Google Sites-Based E-Module for Mathematical Literacy in Social Arithmetic - Win Eka Rahadyani; Munadi; Yoga Prihatin (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aimed to develop an interactive Google Sites-based e-module on social arithmetic and examine its validity, practicality, and effectiveness in supporting junior high school students’ mathematical literacy. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at SMP/MTs in Pemalang Regency during the 2025 academic year, involving 32 eighth-grade students in a limited trial. Data were collected through needs analysis questionnaires, expert validation sheets, student response questionnaires, and mathematical literacy tests. The validity of the product was assessed by material and media experts, while practicality was measured through student responses. Effectiveness was analyzed using pretest–posttest results, paired sample t-test, effect size, and N-Gain. The validation results showed that the e-module was highly valid, with a feasibility score of 92.5% from material experts and 90.3% from media experts. The practicality test showed a positive student response score of 89.6%, indicating that the e-module was easy to use, attractive, and helpful in understanding social arithmetic concepts. The effectiveness test showed an increase in students’ mean score from 56.40 in the pretest to 78.25 in the posttest, with an N-Gain score of 0.52 in the moderate category. These findings indicate that the Google Sites-based interactive e-module is valid, practical, and effective in supporting students’ mathematical literacy, particularly in interpreting contextual problems, formulating mathematical models, applying concepts, and communicating mathematical solutions